Impact of Price on Consumer Loyalty: The Mediating Role of Consumer Satisfaction at Extract Café Pekanbaru - Fadhil, Muhammad; Fadli, Mashur (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to determine the effect of price on customer loyalty through customer satisfaction as an intervening variable at Extract Café Pekanbaru.. Methodology: In this study, a purposive sampling technique was used to sample 100 respondents. The method used was descriptive statistics with a quantitative approach. Measurement models, structural models, and hypothesis testing with SmartPLS4 software analyze data with a Likert scale. Results: the results show that price has a positive and significant effect directly on consumer loyalty with a T-statistic of 2.969> 1.96 and a p-value of 0.003 <0.05. Price has a positive and significant effect directly on customer satisfaction with a T-statistic of 6.729> 1.96 and a p-value of 0.000 <0.05. Customer satisfaction has a positive and significant effect directly on customer loyalty with a T-statistic of 5.965> 1.96 and a p-value of 0.000 <0.05. Customer satisfaction mediates the effect of price on customer loyalty positively and significantly with a T-statistic of 4.562> 1.96 and a p-value of 0.000 <0.05.Findings: In this study, consumer satisfaction is able to mediate the influence of price on consumer loyalty positively and significantly. Novelty: This study uses a data processing application that is different from the previous research, namely using SmartPLS4. Using different dimensions compared to previous research. Originality: This study provides insight into the influence of price on consumer loyalty through consumer satisfaction at Extract Cafe Pekanbaru. The researcher directly distributed the questionnaire to the respondents. Conclusion: With consumer satisfaction obtained from the price is able to increase consumer loyalty. Type of Paper: Empirical Research paper.